Donor Contraindications to Living Kidney Donation: A Single-Center Experience - VELİOĞLU, ARZU; ARIKAN, İZZET HAKKI; TUĞLULAR, ZÜBEYDE SERHAN (ELSEVIER SCIENCE INC, 2015)
Objective. Kidney transplantation is the treatment of choice in end-stage renal disease. In Turkey, the inadequate cadaveric donor supply has resulted in transplantation from living kidney donors (LKD) in 80% of transplant operations. LKD candidates undergo a thorough general medical evaluation and are approved to donate their kidneys only if no contraindication is found. In our study we aimed to investigate the reasons and rate of denial for living kidney donation in our center. Methods. We included all LKD candidates who applied to our center between June 2012 to June 2014. Demographic data, rate of rejection, and the reasons for denial to organ donation were analyzed retrospectively. Results. Of the 97 LKD candidates included in the study, 60 (62%) were unable to donate their kidneys. Among the reasons for denial were hypertension with target organ damage in 30% (n = 18), immunologic reasons in 23% (n = 14), impaired renal function in 20% (n = 12) cardiovascular reasons 13.3% (n = 8), diabetes mellitus in 10% (n = 6), malignity in 10% (n = 6), obesity (body mass index > 35 kg/m(2)) in 5% (n = 3), and miscellaneous in 18.3% (n = 11). There were >1 reasons in 13 candidates. Conclusions. The problems detected in donor candidates offer a possibility for early detection of disorders and increased awareness.
Keywords: DISEASE